2022
DOI: 10.1139/apnm-2021-0414
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the 2019 Canada’s Food Guide: a qualitative study with parents from Southwestern Ontario

Abstract: In January 2019, Health Canada released a revised Canada’s Food Guide (CFG). This study aimed to understand the perceptions of the 2019 CFG among Canadian parents with children aged 2–12 years. From October 2019–January 2020, 8 focus groups with parents from Southwestern Ontario were conducted using a semi-structured interview script focused on understanding perceptions of the 2019 CFG. A hybrid thematic approach with inductive and deductive analyses was used. Forty parents (72.5% mothers, 77.5% white) with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Our study’s findings suggest foods from different cultures may be more challenging to record within the current iteration of iCANPlate TM . As a limitation of the 2019 CFG, other qualitative research on parents has also shown the 2019 CFG does not reflect their traditional foods [ 56 ]. In the absence of cultural food representations on the CFG, incorrect assumptions can be made regarding cultural foods’ health benefits and nutritional values [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study’s findings suggest foods from different cultures may be more challenging to record within the current iteration of iCANPlate TM . As a limitation of the 2019 CFG, other qualitative research on parents has also shown the 2019 CFG does not reflect their traditional foods [ 56 ]. In the absence of cultural food representations on the CFG, incorrect assumptions can be made regarding cultural foods’ health benefits and nutritional values [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant-based proteins, dairy products, and HPF were the most notable sources of confusion. Increasing children's knowledge of the protein foods group, which now includes plant-based proteins and dairy products, is particularly important because previous qualitative research indicated that some parents were unclear on which foods contain plant-based proteins (Barco Leme et al 2022). As parents play an influential role in their children's food knowledge and diets (Atik and Ertekin 2011;Hart et al 2002;Stewart et al 2006;Wijayaratne et al 2020), public health efforts should focus on increasing knowledge of healthy plant-based protein foods among both children and parents (Barco Leme et al 2022;Olfert et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While previous research has examined adults' perceptions (Vanderlee et al 2015) and parents' perceptions (Anderson et al 2015;Barco Leme et al 2022;Patel and Mannion 2021), there is a paucity of research exploring children's perceptions of the 2019 CFG and its revised recommendations. Parents play a critical role in determining children's food knowledge and practices, making it valuable to explore parental perceptions of CFG in the family or home context (Wijayaratne et al 2020;Zarychta et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is also an opportunity for a new universal school food program to address some of the criticism of the 2019 Canada's Food Guide concerning its challenges in reaching culturally diverse, racialized, and Indigenous populations with its dietary recommendations (Barco Leme et al, 2022;Duignan, 2019;Wilson & Shukla, 2020). Some observers were concerned that the Canada's Food Guide image of a "healthy plate" presented in the style of Euro-Western cuisine did not represent diverse understandings of nutrition, food cultures, or cuisines.…”
Section: The School Food Solutionmentioning
confidence: 99%